2011
DOI: 10.1016/j.ridd.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Williams syndrome hypersociability: A neuropsychological study of the amygdala and prefrontal cortex hypotheses

Abstract: Individuals with Williams syndrome display indiscriminate approach towards strangers. Neuroimaging studies conducted so far have linked this social profile to structural and/or functional abnormalities in WS amygdala and prefrontal cortex. In this study, the neuropsychological hypotheses of amygdala and prefrontal cortex involvement in WS hypersociability was explored using three behavioral tasks--facial emotional recognition task, a social approach task and a go no/go task. Thus, a group 15 individuals with W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
(64 reference statements)
5
17
0
Order By: Relevance
“…The results support previous findings with regard to social approach behaviour in WS (Bellugi et al, 1999;Martens et al, 2009;Capitao et al, 2011) …”
Section: Discussionsupporting
confidence: 91%
“…The results support previous findings with regard to social approach behaviour in WS (Bellugi et al, 1999;Martens et al, 2009;Capitao et al, 2011) …”
Section: Discussionsupporting
confidence: 91%
“…These results may be associated with the fact that the facial expression on the trustworthy faces showed no teeth and no definitive smile, and therefore may have appeared more neutral than happy (see Figure 1D). Previous results have shown that individuals with WS rate neutral faces as “medium approachable” (Capitão et al, 2011). These findings might also reflect the previous finding that individuals with WS have more difficulty than controls in interpreting facial expressions (Gagliardi et al, 2003; Plesa-Skwerer et al, 2006; Porter et al, 2007; Capitão et al, 2011), and have atypical eye scanpath patterns when viewing both positive and negative facial expressions (Porter et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…These variations resulted in a total of 80 facial stimuli, creating a 2-by-2 design (trustworthiness by extremity). These stimuli were chosen because they lack many irrelevant features of more naturalistic face images (e.g., hair or accessories) that can distract individuals with WS and interfere with their attention to facial expressions (Martens et al, 2009; Capitão et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…While people with ASD have difficulties with communication, people with Williams syndrome (WS) exhibit hypersociability (Bellugi, Adolphs, Cassady, & Chiles, 1999;Capitao, Sampaio, Fernandez, Sousa, Pinheiro, & Gibcalves, 2011). These conditions have opposite characteristic traits of communication (Asada & Itakura, 2012).…”
Section: Cognitive Science Approachmentioning
confidence: 99%